Gambaran Pengetahuan Remaja Mengenai Kesehatanreproduksi Dan Sikapmenghadapi Masa Pubertas Siswa Kelas Vii Smp Muhammadiyah 10 Surakarta - Mayasari, Siti, Arif Widodo, A.Kep., M.Kes, Okti Sri Purwanti, S.Kep., M.Kep., Ns.Sp.KMB (2016)
Adolescence constitute lifetime of individual which occurs the psychological development of self-discovery. The most striking change and can be seen and felt are the physical changes that occur naturally and sometimes teenagers do not know or are not ready for the physical changes that cause them to be anxious , embarrassed and felt there was a problem with their physical, so that they are unfamiliar with their own bodies. The purpose of research to describe adolescents on reproductive health knowledge and attitudes to face puberty seventh grade students of Muhammadiyah 10 Junior High School Surakarta District .Ttype of this research was qualitative use of phenomenological method. Data collection techniques used by interview autoanamnesa and recorder. Participants of research amounted to eight people. Analysis of the data used thematic analysis. Results of research resulted in five themes of the research objectives. First objective of this research describe knowledge of adolescent students seventh grade of Muhammadiyah 10 Junior High School Surakarta District about reproduction health consists of the reproductive organs and also how to care the reproductive organs is in good and proper to produce a single theme such as knowledge and an understanding of adolescent about reproduction health. The second objective is to determine the attitude of adolescent facing of puberty seventh grade students of Muhammadiyah 10 Junior High School Surakarta District produces two theme,namely I,mpact of physical changes puberty and take control mechanisms of an individual in the face of puberty. The third objective is to describe the experience of adolescents facing puberty seventh grade students of Muhammadiyah 10 Junior High School Surakarta District produces two themes namely the management of reproductive healt care and incompatibility between Knowledge and Management in the treatment of external reproductive Organs. Suggestion for adolescent looking for knowledge about reproductive health, very important to know how to treatment of reproductive organs. Keywords : reproductive health, puberty, knowledge, attitude Consist of fifth nine literature from 2006-2015